The association between emotion malleability beliefs and severe psychological distress stratified by sex, age, and presence of any psychiatric disorders - Sasaki, Yohei; Okubo, Ryo; Takeda, Kazuyoshi; Ikezawa, Satoru; Tabuchi, Takahiro; Shirotsuki, Kentaro (Frontiers in Psychology, 2023)
Background Recent studies have shown an association between psychological distress and emotion malleability beliefs, meaning mindsets about whether one’s emotions are fixed or changeable. However, most studies have not examined the association between these beliefs and sociodemographic factors. Methods A nationwide cross-sectional Internet survey of residents of Japan aged 15–79 years was conducted using sampling weights for national estimates to investigate the association between emotion malleability beliefs and sociodemographic factors and between fixed beliefs and severe psychological distress (SPD). SPD was defined as a Kessler 6 Scale score of ≥13. Adjusted odds ratios for SPD were calculated considering potential confounders. Further analyses were stratified by sex, age and presence of any psychiatric disorder. Results The analysis included 23,142 participants (female, 48.64%). Fixed beliefs were associated with female sex, age < 45 years, and presence of psychiatric disorders. These beliefs were associated with SPD, and additional analysis showed stronger associations with SPD among female respondents, respondents aged 45–59 years, and those aged ≥60 years. Conclusion Results indicate that female sex, age < 45 years, and current mental disorders were associated with fixed emotion malleability beliefs. Associations between fixed emotion malleability beliefs and SPD were particularly strong among female respondents and people aged ≥45 years compared with the general population. Our study extends the association between emotion malleability beliefs and psychological health to the general population. Future studies should explore mechanisms underlying individual differences in emotion beliefs.